Voiture minimum : Le Corbusier and the automobile - Amado Lorenzo, Antonio, 1956- (MIT Press, 2011)
"Le Corbusier, who famously called a house 'a machine for living,' was fascinated--even obsessed--by another kind of machine, the automobile. His writings were strewn with references to autos ... In his 'white phase' of the twenties and thirties, he insisted that his buildings be photographed with a modern automobile in the foreground. Le Corbusier moved beyond the theoretical in 1936, entering (with his cousin Pierre Jeanneret) an automobile design competition, submitting plans for 'a minimalist vehicle for maximum functionality,' the Voiture Minimum. Despite Le Corbusier's energetic promotion of his design to several important automakers, the Voiture Minimum was never mass-produced. This book is the first to tell the full and true story of Le Corbusier's adventure in automobile design. Architect Antonio Amado describes the project in detail, linking it to Le Corbusier's architectural work, to Modernist utopian urban visions, and to the automobile design projects of other architects including Walter Gropius and Frank Lloyd Wright. The story is supported by many images and documents, including architects' favorite cars, sketches and models of the Voiture Minimum, and copies of Le Corbusier's correspondence with prospective manufacturers."-- Anotace od vydavatele
Keywords: Le Corbusier, -- 1887-1965; průmyslový design; automobilový design; industrial design; automobile design; plány; biografie; studie; plans; biography; studies